ANALISISTENTANG PENYALAHGUNAAN NARKOTIKA DI KALANGAN SISWA DITINJAU DARI SEGI KRIMINOLOGI - Indra Kumalasari M. (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2018)
AbstractNarcotics abuse nowadays involves many teenagers, especially junior high school students. In 2017, the urine test result conducted by BNN (Indonesian National Narcotics Agency) in Asahan District finds that students whose urine tests are positive consume the first narcotics group marijuana. This research was conducted qualitatively with case studies. Data collection is done by In-depth Interview, documentation, and observation. Informants were selected by purposive sampling. The result of the study shows that the students positively consuming narcotics receive unfavorable treatment from school, and they do not get criminal penalties because they are considered as in the trial and error stage. However, the assessment by BNN in Asahan District proposes that the students should take the ongoing rehabilitation and counseling guidance accompanied by schools, parents and a doctor and psychologist of BNN in Asahan District. Keywords: criminology, narcotics, student